2021
DOI: 10.3389/fcell.2020.624337
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Acellular Cartilaginous and Dermal Matrixes as Tissue Engineering Scaffolds for Cartilage Regeneration

Abstract: An acellular matrix (AM) as a kind of natural biomaterial is gaining increasing attention in tissue engineering applications. An acellular cartilaginous matrix (ACM) and acellular dermal matrix (ADM) are two kinds of the most widely used AMs in cartilage tissue engineering. However, there is still debate over which of these AMs achieves optimal cartilage regeneration, especially in immunocompetent large animals. In the current study, we fabricated porous ADM and ACM scaffolds by a freeze-drying method and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…This study demonstrated the feasibility of in vitro cartilage regeneration using chondrocyte-loaded hydrogel, but failed to provide related evidence about the chondrogenic regulation of BMSCs. In the concurrent study, we adopted the collagenase digestion strategy as a water-soluble treatment to decrease the negative effect of type Ⅱ collagen triggering inflammation [ 50 , 51 ]. Additionally, ColMA derived from skin was further added to counteract the dramatic loss of collagen components caused by collagenase digestion ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated the feasibility of in vitro cartilage regeneration using chondrocyte-loaded hydrogel, but failed to provide related evidence about the chondrogenic regulation of BMSCs. In the concurrent study, we adopted the collagenase digestion strategy as a water-soluble treatment to decrease the negative effect of type Ⅱ collagen triggering inflammation [ 50 , 51 ]. Additionally, ColMA derived from skin was further added to counteract the dramatic loss of collagen components caused by collagenase digestion ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The repair of craniofacial cartilage defect has always been a great clinical challenge ( Raub et al, 2013 ; Xue et al, 2018 ), and recent development of tissue engineering technology has provided a promising strategy for repair and reconstruction of various cartilage defects ( Makris et al, 2015 ; Kwon et al, 2019 ; Wei et al, 2021 ). By obtaining a small piece of autologous cartilage for chondrocyte isolation, followed by in vitro amplification, large-volume autologous cartilage regeneration can be achieved ( Armiento et al, 2018 ; Wang et al, 2020 ; Liau et al, 2021 ). However, up to now, how to construct three-dimensional (3D) cartilage with specific shape and mechanical strength for the repair of craniofacial cartilage defects remains a huge challenge ( Xia et al, 2018 ; Chae et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decellularization effect assessment of the AOM scaffold: Hematoxylin and eosin (HE) staining, 4’,6-diamidino-2-phenylindole (DAPI) staining, and DNA quantitative analysis were used to evaluate whether the cells were removed completely in the AOM scaffold [ 15 ]. Then, the glycosaminoglycan (GAG) content, total collagen content, and mechanical strength of the samples before and after acellularization were quantitatively analyzed [ 15 , 39 ]. Galactose-α-1,3-galactose (alpha-gal) content of the samples before and after decellularization was examined by using antigen quantitative detection kit (70101, Sanyao Science, China) according to the method provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%